Etyczne i ekonomiczne aspekty kategorii zasoby społeczne Stanisława Głąbińskiego - Szymański, Zdzisław (Annales. Etyka w Życiu Gospodarczym, 2010)
Stanisław Głąbiński (1862–1941) professor at the Lvov University, the author of a two volume work entitled „National economics” is a representative of the historical-national trend in Polish economics. The subject matter of his concept of national economics is the national economy which is a higher rank entity, encompassing all economic entities in the country that are related materially and spiritually. Bonds that link individuals into a higher rank entity, i.e. a nation, are reflected in the term ‘social resources’. Głąbiński understands them as moral and material heritage of past generations that influences attitudes of the contemporary generation. He divides them into moral and material resources, and especially emphasizes the importance of the former ones. In the concept of moral resources, Głąbiński included his claims concerning the whole socio-ethical conditions of economic processes. He appreciated the influence exerted by the changes in the ethical viewpoint of the society on the economic activity as well as on the shaping of the sense of duty towards the whole society. Special emphasis placed in Głąbiński’s economic theory on the role of ethical motives undoubtedly springs from the influence exerted by the German historical school and, in particular, by Bruno Hildebrand. It also is a result of the effect of Polish economic thought including in particular the views of Fryderyk Skarbek and Józef Supiński. According to Głąbiński, the most important constituent element of material resources was finance, understood by him as stocks of economic goods.